FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA - Jamal Muhyidin; Sri Ambarwati; Widyaningsih Azizah (FEB-UP Press, 2021)
This study aims to determine the effect of managerial ownership, independent board of commissioners, earnings quality and firm size on firm value. The data is secondary data from annual report. The population is manufacturing companies sector basic industry and chemical listed on Indonesia Stock Exchange (IDX) for the period 2017-2019. The research sample consisted of 17 companies using purposive sampling. Hypothesis testing used panel data regression analysis by using Eviews10 software application. The results of this study indicate that firm size had a significant negative effect on firm value, managerial ownership, independent board of commissioners, and earnings quality had no effect on firm value.